Optimasi Penyerapan Ion Logam Pb2+ Menggunakan Kulit Manggis (Garcinia Mangostana L.) Dengan Matode Batch - Husna, Miftahul; Kurniawati, Desy (Departemen Kimia FMIPA UNP, 2024)
Pb2+ ion is a metal that is toxic and harmful to the health of the human body and causes mental disorders and can cause environmental pollution. Biosorption is to release heavy metal ions by utilizing various natural ingredients. The purpose of this study was to determine the optimum conditions for mangosteen peel activated with NaOH using variations in particle size, agitation speed and absorption capacity of Pb2+ metal ions using a batch method. The results of this study resulted in optimum conditions for the absorption of Pb2+ ions at a particle size of 180 μm and a stirring speed of 200 rpm with an absorption capacity of 31.25 mg/g. Biosorption using mangosteen peel has been shown to be able to absorb Pb2+ ions using the batch method.